Iron supplementation prevents a decline in iron stores and enhances strength performance in elite female volleyball players during the competitive season - Mielgo-Ayuso, J.; Zourdos, M. C.; Calleja-Gonzalez, J.; Urdampilleta, A.; Ostojicf, S. (Applied Physiology, Nutrition, and Metabolism, 2015)
The primary aim of this study was to examine the effects of 11 weeks of iron supplementation on hematological and strength markers in elite female volleyball players. Twenty-two volleyball players (aged 27.0 ± 5.6 years) from 2 Spanish First National League teams participated and were counterbalanced into 1 of 2 groups based upon iron status: (i) control group (CG, n = 11); or (ii) iron treatment group (ITG, n = 11), which received 325 mg/day of ferrous sulphate daily. Subjects performed their team`s regimen of training or match play every day. Both groups were tested for hematological and strength levels at 2 points: (i) baseline (T0, before preseason) and (ii) 11 weeks later (T11, post-testing). Hematological parameters were serum iron (sFe), serum ferritin (FER), transferrin saturation index (TSI), and hemoglobin (Hb); strength assessments were bench press, military press, half-squat, power clean, clean and jerk, and pull-over. CG experienced a significant decrease (p < 0.05) for sFe (T0, 112.7 ± 31.5; T11, 69.0 ± 20.5 µg/dL; -33.9%), FER (T0, 60.2 ± 28.6; T11, 38.2 ± 16.4 ng/mL; -34.6%), TSI (T0, 29.4% ± 9.5%; T11, 17.4% ± 5.1%; -35.3%), and Hb (T0, 14.1 ± 1.0; T11, 13.0 ± 0.8 g/L; -7.44%); however, ITG experienced no changes (p > 0.05). Consequently, in ITG all hematological parameters were significantly greater (p < 0.05) than CG at T11. There was greater (p < 0.05) percent increase in the clean and jerk (CG: +5.1% ± 20.9 vs. ITG: +29.0% ± 21.3%), power clean (CG: -5.8% ± 30.3% vs. ITG: +44.6% ± 56.6%), and total mean strength (CG: +10.9% ± 3.2% vs. ITG: +26.2% ± 3.6%) in ITG. Our findings suggest that oral iron supplementation prevents iron loss and enhances strength in female volleyball players during the competitive season.